School Debate Societies and Their Contribution to the Development of Socio-Emotional Skills: A Case Study in Latin America - Quiroz-Millán, Luz Elena (2025)
Aim. This research article presents the results of a study focused on determining the contribution of school debate societies in the development of socio-emotional skills in ten public and private educational institutions in four Latin American countries. Methodology. For the purpose of operationalizing this objective, the research was conducted using a qualitative approach and a multiple case study design to obtain a broader perspective of the object of study. Accordingly, techniques and instruments such as questionnaires and in-depth interviews, discussion groups, and participant observation were applied during school debate sessions with 118 students and 12 teachers from the targeted organizations throughout the different phases involved in the selected design. Results. Among the main results, we highlight that debating societies are conducive scenarios for the development of skills related to assertiveness, self-regulation, empathy, active listening, and critical thinking, which results in the cultivation of values and attitudes from the promotion of recognition, respect, and responsibility towards others. Conclusions. Based on these findings, it became evident that debate societies function as educational spaces that help shape citizens capable of participating actively and responsibly in democratic life. In this regard, the diversity and plurality present in debates are consolidated as pedagogical resources that enhance learning and democratic coexistence.